A verification and validation exercise for the numerical resource assessment of tidal currents in the Tagus estuary (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy represents a dependable and predictable form of renewable energy. Due to its site-specific nature, precise resource assessment is essential. Nowadays, numerical models serve as a widely-used and cost-effective method for resource assessment, offering flow data across extensive areas of interest. However, the credibility of these models must be rigorously evaluated. In this work, the application of a verification tool is presented to estimate the numerical uncertainty of flow simulations with MOHID Water, a three-dimensional baroclinic free-surface model targeted at simulating coastal and estuarine hydrodynamics. The Tagus estuary, one of the largest estuaries in Western Europe, serves as test case. The numerical uncertainty of the simulated current speed and direction is estimated at three potential sites for hydrokinetic energy extraction, where experimental drifter data is available for validation purpose. It is observed that the numerical data obtained from the grid refinement study contains a significant amount of scatter, mostly resulting in conservative uncertainty estimates. Nevertheless, taking into account both numerical and experimental uncertainties, the numerical model captures well the experimental trends for the majority of the test data.